1973
DOI: 10.1139/v73-154
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochlores. IX. Partially Oxidized Sn2Nb2O7 and Sn2Ta2O7: A Mössbauer Study of Sn(II,IV) Compounds

Abstract: Partially oxidized tin(I1) niobate and tantalate ~jyrochlores are homogeneous cubic phases. They have been shown by Mossbauer '19Sn spectroscopy to contain both Sn(I1) and Sn(1V). Each valency state is segregated on its own, crystallographically distinct sublattice as a consequence of the size disparity of Sn2+ and Sn4+ atoms. The strong temperature dependence of the Mossbauer Sn2+:Sn4+ area ratios between room temperature and 4.2"K indicates that the recoil-free fractions of the SnZ+ and Sn4+ atoms in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…For instance, the Mössbauer intensity depends on the recoil-free fraction of Sn nuclei, and the fraction is temperature dependent. Stewart et al reported [18] the Mössbauer spectra at 4.2-290 K of Sn-Ta-O pyrochlore, which was iso-structure with the present Sn-Nb-O pyrochlore, and showed the smaller recoil-free fraction of Sn II than that of Sn IV at high temperature. Because the present spectrum was recorded at room temperature, the recoil-free fraction of Sn II was smaller than that of Sn IV as expected the results for Sn-Ta-O pyrochlore.…”
Section: Resultsmentioning
confidence: 65%
“…For instance, the Mössbauer intensity depends on the recoil-free fraction of Sn nuclei, and the fraction is temperature dependent. Stewart et al reported [18] the Mössbauer spectra at 4.2-290 K of Sn-Ta-O pyrochlore, which was iso-structure with the present Sn-Nb-O pyrochlore, and showed the smaller recoil-free fraction of Sn II than that of Sn IV at high temperature. Because the present spectrum was recorded at room temperature, the recoil-free fraction of Sn II was smaller than that of Sn IV as expected the results for Sn-Ta-O pyrochlore.…”
Section: Resultsmentioning
confidence: 65%
“…Since density measurements on the final, homogeneous prepamtions (samples ii) indicated incompletely occupied unit cells, the necessity of determining whether mixed valency states were present became apparent. Results of a Mossbauer 12'Sb investigation will be communicated in another paper of this series (33).…”
Section: Structure Refinementsmentioning
confidence: 97%
“…However, the errors associated with the peak areas are sufficiently large that any small differences in the recoil-free fractions would not significantly alter the Sb"':Sbv ratio. It is of interest to note that in a recent investigation of non-stoichiometric pyrochlores resembling Sb60,, and containing simultaneously Sn2+ and Sn4+, the recoil-free fractions of these two valency species have been shown to differ by less than 10% (35).…”
Section: X-ray Diffractionmentioning
confidence: 99%